Microfluidic Impedance Cytometry for Single‐Cell Particulate Inorganic Carbon:Particulate Organic Carbon Measurements of Calcifying Algae. Issue 3 (7th December 2022) - de Bruijn, Douwe S.; Van de Waal, Dedmer B.; Helmsing, Nico R.; Olthuis, Wouter; van den Berg, Albert
Abstract: Calcifying algae, like coccolithophores, greatly contribute to the oceanic carbon cycle and are therefore of particular interest for ocean carbon models. They play a key role in two processes that are important for the effective CO2 flux: The organic carbon pump (photosynthesis) and the inorganic carbon pump (calcification). The relative contribution of calcification and photosynthesis can be measured in algae by the amount of particulate inorganic carbon (PIC) and particulate organic carbon (POC). A microfluidic impedance cytometer is presented, enabling non‐invasive and high‐throughput assessment of the calcification state of single coccolithophore cells. Gradual modification of the exoskeleton by acidification results in a strong linear fit ( R 2 = 0.98) between the average electrical phase and the PIC:POC ratio of the coccolithophore Emiliania huxleyi 920/9. The effect of different CO2 treatments on the PIC:POC ratio, however, is inconclusive, indicating that there is no strong effect observed for this particular strain. Lower PIC:POC ratios in cultures that grew to higher cell densities are found, which are also recorded with the impedance‐based PIC:POC sensor. The development of this new quantification tool for small volumes paves the way for high‐throughput analysis while applying multi‐variable environmental stressors to support projections of the future marine carbon cycle. Abstract : Calcifying algae play an important role in the ocean carbon cycle. The calcification state of these algae is studied at single‐cell level using microfluidic impedance cytometry. This work demonstrates that the algal calcification state can be assessed by the electrical phase. Additionally, the influence of changes in the seawater carbonate chemistry on the calcification state is investigated.